The Effectiveness of Using A Maternity Pillow and Coffee Aromatherapy on Sleep Quality in Third-Trimester Pregnant Women - Ika Lestari Sitorus; Fahnidar Rahma (GLOBAL HEALTH SCIENCE GROUP, 2026)
The maternal mortality rate (MMR) in Indonesia remains high at 305 per 100,000 live births, far from the national target of 183 per 100,000 live births by 2024. Pregnancy complications such as preeclampsia, gestational diabetes, and preterm labor are the main causes of high maternal morbidity and mortality. One contributing factor is the delay in early detection due to limited access and resources of health workers in primary care facilities. This research aims to develop Gestasi Care , a web-based digital application designed to support early detection of pregnancy complications, monitor antenatal care (ANC) schedules, and provide education to pregnant women. Method: The research method used was Research and Development (R&D) with a waterfall System Development Life Cycle (SDLC) approach. The research stages included needs analysis, prototype design, initial data collection through a survey at the Sidodadi Community Health Center, and initial application trials with midwives and doctors. A prototype application has been developed with key features including pregnancy risk screening (low, medium, and high categories), ANC and ultrasound schedule reminders, digital medical records, teleconsultation, and trimester-based education. The application is currently undergoing content validation and preparation for a limited field trial to assess feasibility and user acceptance. Gestation Care has the potential to be an innovative digital-based solution to strengthen maternal health services in primary care facilities, increase the effectiveness of early detection of pregnancy complications, and support efforts to reduce maternal mortality in Indonesia.